2008
DOI: 10.1007/s00018-008-8548-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of P-glycoprotein/cellular prion protein interaction in multidrug-resistant breast cancer cells treated with paclitaxel

Abstract: We previously reported that treatment with P-glycoprotein (P-gp) substrates promotes in vitro invasion in multidrug-resistant (MDR) breast cancer cells. This effect is initiated by the P-gp pump function and mediated by interaction of P-gp with some unknown component(s). However, the underlying mechanism(s) remains poorly understood. Here we confirm a novel physical interaction between P-gp and cellular prion protein (PrP(c)). Blocking P-gp activity or depletion of PrP(c) inhibited paclitaxel (P-gp substrate)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 30 publications
1
53
0
2
Order By: Relevance
“…Previous studies on PrP c in cancer are generally consistent with the notion that PrP c expression increases resistance to cytotoxicity (27)(28)(29)(30)(31). One of the ways to eliminate this is via inhibition of glucose by various therapeutic drugs (32).…”
Section: Effect Of Fucoidan On Ht29 Colon Cancer Cell Apoptosis Htmentioning
confidence: 52%
“…Previous studies on PrP c in cancer are generally consistent with the notion that PrP c expression increases resistance to cytotoxicity (27)(28)(29)(30)(31). One of the ways to eliminate this is via inhibition of glucose by various therapeutic drugs (32).…”
Section: Effect Of Fucoidan On Ht29 Colon Cancer Cell Apoptosis Htmentioning
confidence: 52%
“…The molecular mechanism of multi-drug resistance (MDR) in cancer cells has long been associated with P-glycoprotein, an energy-dependent multi-drug efflux pump (reviewed in [154]). Recently, it was shown that PrP interacts with P-glycoprotein and is essential for drug resistance in breast cancer cells [155]. Several studies have also functionally linked MDR and tumor metastasis [156–159].…”
Section: Implications For Prevention Early Diagnosis and Targeted Tmentioning
confidence: 99%
“…Both PrP C and HOP also modulate tumorigenesis, affecting the progression and maintenance of different types of cancers [8]. PrP C associates with a poor clinical outcome and survival in pancreatic ductal adenocarcinoma and melanoma [9, 10], and with invasion and metastasis in gastric and breast cancers [8, 11, 12]. Depleting PrP C inhibits growth, promotes programmed cell death in gliomas [13], and sensitizes tumor cells to cytotoxic drugs [14].…”
Section: Introductionmentioning
confidence: 99%